2003
DOI: 10.1161/01.res.0000083812.30141.74
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Transfusion of Endothelial Progenitor Cells Reduces Neointima Formation After Vascular Injury

Abstract: Abstract-Endothelial cell damage is one important pathophysiological step of atherosclerosis and restenosis after angioplasty. Accelerated reendothelialization impairs neointima formation. We evaluated the role of intravenously transfused endothelial progenitor cells (EPCs) on reendothelialization and neointima formation in a mouse model of arterial injury. 4 or transplanted stem cells 5-9 on remodeling after myocardial infarction. Special attention has been directed to endothelial progenitor cells (EPCs), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
489
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(514 citation statements)
references
References 38 publications
14
489
0
11
Order By: Relevance
“…Exactly how c-kit-immunopositive cells participate in this process is unknown; moreover, we cannot ignore the possibility that they may simply serve as an incidental marker of this disease process. Although we are unable to go beyond these postulates, there are circumstantial data in support of the notion that circulating progenitor cells may participate in vascular repair and lesion formation (3,10,23,25,32). However, as noted previously, the precise nature of endothelial and smooth muscle precursor cells and markers that might uniquely identify these cell types remains unclear (11).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Exactly how c-kit-immunopositive cells participate in this process is unknown; moreover, we cannot ignore the possibility that they may simply serve as an incidental marker of this disease process. Although we are unable to go beyond these postulates, there are circumstantial data in support of the notion that circulating progenitor cells may participate in vascular repair and lesion formation (3,10,23,25,32). However, as noted previously, the precise nature of endothelial and smooth muscle precursor cells and markers that might uniquely identify these cell types remains unclear (11).…”
Section: Discussionmentioning
confidence: 71%
“…Rehman and colleagues (24) suggest that the absence of specific endothelial or progenitor cell markers on cultured PBMCs gives reason to label these cells as cultured angiogenic cells (CACs), rather than EPCs. Recent studies show that intravenous transfusions of CACs mitigate neointima formation after vascular injury and prevent atherosclerosis in murine models (23,32).…”
mentioning
confidence: 99%
“…An elevated apoptotic rate of mature vascular endothelial cells in conjunction with an impaired regenerative capacity of CPC might further aggravate vascular alterations 55, 59, 60. Current knowledge of endothelial dysfunction in vascular disease is discussed in detail by Vanhoutte et al 61…”
Section: Vascular Alterations In Cadmentioning
confidence: 99%
“…Impaired function of EPCs is related to endothelial dysfunction (23). Some studies have indicated that EPCs are involved in repair of damaged endothelium and attenuate the development of atherosclerosis (24)(25)(26). Several pathological conditions, including hypertension, diabetes, and atherosclerosis, can impair the endothelial cell by oxidative stress (27).…”
Section: Discussionmentioning
confidence: 99%